2016
DOI: 10.1007/s12471-016-0887-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radial versus femoral artery access in patients with acute myocardial infarction: A large centre prospective registry

Abstract: AimThis study sought to assess whether radial artery access improves clinical outcomes in patients presenting with acute myocardial infarction compared with femoral artery access.MethodsThis is a single-centre, prospective observational registry of all STEMI and NSTEMI patients who underwent coronary angiography and/or primary PCI in the period January 2010 to December 2013. Primary endpoint was 30-day all-cause mortality. Choice of access was left to the discretion of the cardiologist. Differences in the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Radial access as the initial choice of vascular access has been increasing in coronary interventional procedures mainly due to decreased incidence of vascular complications and improved patient outcomes when compared to femoral access. 2,5 It has also been suggested that radial approach is more cost effective (in terms of shorter hospital stays and less access site complications) translating to better cost effectiveness. 7 Our retrospective study gives a sample of a real world patient characteristics that influence physician preference of initial femoral versus radial access, and could be helpful in the absence of specific guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radial access as the initial choice of vascular access has been increasing in coronary interventional procedures mainly due to decreased incidence of vascular complications and improved patient outcomes when compared to femoral access. 2,5 It has also been suggested that radial approach is more cost effective (in terms of shorter hospital stays and less access site complications) translating to better cost effectiveness. 7 Our retrospective study gives a sample of a real world patient characteristics that influence physician preference of initial femoral versus radial access, and could be helpful in the absence of specific guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Radial access as the initial choice of vascular access has been increasing in coronary interventional procedures mainly due to decreased incidence of vascular complications and improved patient outcomes when compared to femoral access . It has also been suggested that radial approach is more cost effective (in terms of shorter hospital stays and less access site complications) translating to better cost effectiveness .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that femoral access is associated with poorer clinical outcomes in patients with ACS treated using PCI [21]. This could be explained mostly by the fact that patients with femoral access are often in a severe clinical state and undergo more complicated and demanding procedures.…”
Section: Acs -Acute Coronary Syndrome Ami -Acute Myocardial Infarctimentioning
confidence: 99%
“…The radial artery (RA) has gained worldwide popularity as the preferred vascular access for cardiac catheterization procedures, 1–5 offering advantages such as reduced cost, bleeding, and complications, along with improved patient comfort and early ambulation, as supported by systematic reviews and meta‐analyses 6,7 . However mastering RA access can be challenging due to its steep learning curve 8 .…”
Section: Introductionmentioning
confidence: 99%